Oxidação de sulfetos promovida por materiais carbonáceos ativados - Bruno Rocha Santos Lemos (2010)
In this study, the use of activated carbons (ACs) to promote the oxidation of sulfide ions in solution was evaluated. Raman, IR, UV-Vis, XRD and TG/DTA data showed that the oxidation of sulfides led to the formation of polysulfides, especially S22- and products containing sulfur in higher oxidation states, such as thiosulfate, sulfite and sulfates. The ACs used in the oxidation of sulfides were also analyzed by Raman, IR and potentiometric titration. It was observed that the surface of the ACs did not change significantly after the oxidation reaction. Preliminary studies on the sulfide oxidation kinetics in aqueous solution suggested that the reaction follows a first order kinetics with relation to sulfides and AC.ACs modified by oxidation with HNO3 or thermal treatment under vacuum at 900 °C suggested that oxygen groups on the AC surface promote the reaction. Finally, a simplified mechanism was proposed where the oxidation of ions S2- takes place on the carbon surface which plays a role of electron receptor and transfer. The sulfide reactive species on carbon surface can react with S2- or H2O leading to the formation of S22- or SOx2-, respectively.